Controlling the growth of Bi(110) and Bi(111) films on an insulating substrate. (16th March 2017) - Jankowski, Maciej; Kamiński, Daniel; Vergeer, Kurt; Mirolo, Marta; Carla, Francesco; Rijnders, Guus; Bollmann, Tjeerd R J
Abstract: We demonstrate the controlled growth of Bi(110) and Bi(111) films on an α -Al2 O3 (0001) substrate by surface x-ray diffraction and x-ray reflectivity using synchrotron radiation. At temperatures as low as 40 K, unanticipated pseudo-cubic Bi(110) films are grown with thicknesses ranging from a few to tens of nanometers. The roughness at the film–vacuum as well as the film–substrate interface, can be reduced by mild heating, where a crystallographic orientation transition of Bi(110) towards Bi(111) is observed at 400 K. From 450 K onwards high quality ultrasmooth Bi(111) films form. Growth around the transition temperature results in the growth of competing Bi(110) and Bi(111) domains.